The protective effect of the aqueous extract of parsley (Petroselinum sativum ) seeds on experimentally – induced oxidative stress in rats - Khudiar, K. K.; Abdullah, B. N.; Al-Mzaien, K. A. (The Iraqi Journal of Veterinary Medicine, 2021)
In this study, the potential protective effect of aqueous extract of parsley (Petroselinum sativum) seeds against hydrogen peroxide (H2O2) – induced oxidative stress in male rats was assessed. Three groups of male albino rats were randomly divided (n=7) and were handled for twenty-eight days as follows: rats in group I served as control; animals in group || were provided with drinking water containing 0.5% H2O2 and those in group III received orally 8 mg/100 gm B.W. of aqueous extract of parsley seeds plus 0.5% H2O2 in drinking water. After four weeks experimental period, a significant increase in lipid peroxidation products (MDA), and decrease in glutathione (GSH) concentrations were observed in plasma, kidney, liver and heart tissues of H2O2 treated animals as compared with the control group. These biomarkers (GSH and MDA) are interrelated and indicate the occurrence of oxidative stress. Plasma total cholesterol (TC) concentration was significantly increased in H2O2 treated rats. By administration of aqueous extract of parsley along with H2O2, plasma and tissue GSH levels were significantly increased while the elevation in MDA level was diminished in plasma and different tissues examined. A decrease in plasma cholesterol concentration was recorded in H2O2 and parsley treated group as compared with the control one and H2O2 treated groups. These results indicate that aqueous extract of parsley have hypocholesterolemic and antioxidant effect.